Rare systemic mycoses in cats: blastomycosis, histoplasmosis and coccidioidomycosis: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Lloret, Albert; Hartmann, Katrin; Pennisi, Maria Grazia; Ferrer, Lluis; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Rare fungal infections, including those hitherto not reported in Europe, may occur sporadically in non-endemic areas, or imported cases may be seen. Infections: Blastomycosis is mainly seen in North America; no cases have been reported in Europe. Histoplasmosis, which is endemic in the eastern US, Central and South America, has been diagnosed in Japan and Europe. Coccidioidomycosis is endemic in the southwestern US, Central and South America; only one imported case has been reported in Europe. The primary mode of transmission is inhalation of conidia or spores from the environment. Disease signs: Most feline cases present with a combination of clinical signs (mainly respiratory, along with skin, eye, central nervous system and bone). Lymphadenopathy and systemic signs may be present. Diagnosis: Diagnosis is based on fungal detection by cytology and/or histology. Commercial laboratories do not routinely perform fungal culture. Diagnosis of coccidioidomycosis, which is more difficult, may be supported by antibody detection. Treatment: Treatment consists of prolonged systemic antifungal therapy, with itraconazole as the first-choice agent for histoplasmosis and blastomycosis. The prognosis is good if owner compliance is adequate and adverse drug effects do not occur. Prevention: Cat owners travelling to endemic areas should be warned about these diseases. There is no zoonotic risk.